2016
DOI: 10.18052/www.scipress.com/ijppe.2.5
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Docking Study of N-Ferrocenylmethylnitroanilines as Potential Anticancer Drugs

Abstract: In the present study, the interaction of the protein structure of Escherichia coli DNA Gyrase-A (EcGyr-A) extracted from protein data bank (PDB Code: 1AB4) with ligands Nferrocenylmethyl-2-nitroaniline (2FMNA), N-ferrocenylmethyl-3-nitroaniline (3FMNA) and Nferrocenylmethyl-4-nitroaniline (4FMNA) were investigated by performing docking studies using the Molegro Virtual Docker (MVD) software. The results obtained showed that the best poses which is derived from MolDock score for Escherichia coli DNA Gyrase-A we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The binding site was set inside a restriction sphere of 20 Å radius, also using MVD. All other software parameters for docking were set to the default values (Lanez & Lanez, 2016). The parameters were as follows: the 'MolDock SE' searching algorithm was used with the number of runs set to 10 using a maximum of 1500 iterations and a total population size of 50.…”
Section: Antibacterial Docking Studies and Assessment Of Antimicrobial Assaymentioning
confidence: 99%
“…The binding site was set inside a restriction sphere of 20 Å radius, also using MVD. All other software parameters for docking were set to the default values (Lanez & Lanez, 2016). The parameters were as follows: the 'MolDock SE' searching algorithm was used with the number of runs set to 10 using a maximum of 1500 iterations and a total population size of 50.…”
Section: Antibacterial Docking Studies and Assessment Of Antimicrobial Assaymentioning
confidence: 99%
“…It is made up of GyrA subunits where the DNA binding domain is located and GyrB subunits which are responsible for ATP activity. However, Gyr A or Gry B can be blocked by these inhibitors for the termination of the DNA replication or to prevent their binding to the DNA [5]. The concept of computational chemistry like computer-aided drug design (CADD) might save the time of discovering or designing new compounds with better potency, and also reduce the cost of synthesis [6].…”
Section: Introductionmentioning
confidence: 99%
“…Computationally, the interaction between the chemical compounds within some positions of the proteins in three dimensions may be predicted [1]. Many spectroscopic and thermodynamic studies were reported and investigated of various chemical compounds using molecular docking methods such as nitro aniline [2][3][4], vanillins [5 some diazo dyes [11][12][13][14][15], and steroid glycoside [16].…”
Section: Introductionmentioning
confidence: 99%